2012
DOI: 10.4172/2157-7099.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Subcutaneous Metastatic Deposits by Fine Needle Aspiration

Abstract: Objectives: Subcutaneous tissue is an uncommon site of metastasis. Overall it can be seen in 0.8-4% of the malignancies. Fine Needle Aspiration Cytology (FNAC) is a method for the diagnosis of subcutaneous metastasis and to exclude other differential diagnoses such as primary cutaneous tumors or inflammatory process. In this study we want to report our experience with Fine Needle Aspiration (FNA) of subcutaneous metastasis in 25 patients with known malignancy.Study design: During 3 years, among more than 10000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…and many studies had reported higher incidence of cutaneous metastases in males rather than females. 2,7,9,10 However, some studies had reported similar age range as the present study with slightly higher incidence in females. 1,5,6,9 In our study, lungs was the most common primary site in males (25%), however, in females majority of the cutaneous metastases were from malignancies in the breast (13.9%) and ovary (13.9%) (Table2).…”
Section: Primary Tumoursupporting
confidence: 80%
“…and many studies had reported higher incidence of cutaneous metastases in males rather than females. 2,7,9,10 However, some studies had reported similar age range as the present study with slightly higher incidence in females. 1,5,6,9 In our study, lungs was the most common primary site in males (25%), however, in females majority of the cutaneous metastases were from malignancies in the breast (13.9%) and ovary (13.9%) (Table2).…”
Section: Primary Tumoursupporting
confidence: 80%
“…Such lesions may indicate failure of ongoing therapy or recurrence of a cancer which was previously cured or, rarely it may be the first sign of unsuspected malignancy. 6 Subcutaneous metastases of malignancies can be secondary to direct extension from tumor or by lymphatic or vascular route. 4 Metastases can occur everywhere in the subcutaneous tissue but it usually tends to be close to the primary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5 FNAC is an excellent, safe, rapid, minimally invasive and simple method for early diagnosis of such cases as the lesions are easily accessible and palpable. 6,7 for Fine needle aspiration in cytology OPD, 25 cases were diagnosed as cutaneous and subcutaneous lesions. Clinical history and details of all relevant investigations performed was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…5 FNAC not only helps in early diagnosis & prompt initial evaluation & treatment of cutaneous metastasis with known primary but also offers an accurate & non invasive method for diagnosis of metastasis. 7 Further use of LBC helps in diagnosing primary with help of ICC & in some cases prognosis of tumour. 8 In most of patients subcutaneous metastasis reveals a terminal stage of illness so using a non invasive method for diagnosis or exclusion of metastasis is crucial.…”
Section: Discussionmentioning
confidence: 99%